Collaborative Governance in Strengthening Hospital Environmental Security: The Phenomenon of Overcrowding of Visitors at Kaimana Hospital - Hasnah Tapa; Ika Devi Pramudiana; Dian Feriswara; Feri Ramadhan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study analyzes the application of collaborative governance in overcoming the phenomenon of overcrowding of visitors and its impact on environmental security at Kaimana Hospital, West Papua. The background of the research is based on the imbalance in the capacity of hospital infrastructure (serving 65,490 people) with the high number of visits, exacerbated by the habit of the community transporting patients en masse and the massive use of JKN services. The descriptive qualitative method is used with data collection techniques through semi-structured interviews, observations, and visual documentation. The analysis refers to the theory of Ansell and Gash (2008) which includes starting conditions, institutional design, facilitative leadership, collaborative process, and outcome. The results of the study show that efforts such as limiting visiting hours and the construction of halfway houses are not optimal due to less participatory policy design, lack of structured dialogue between stakeholders, and top-down leadership. Overcrowding is triggered by narrow waiting rooms, limited facilities, and the disintegration of the queue system. Despite collaborative initiatives, the results are still partial due to weak cross-sector coordination and low community participation. Strategic suggestions include infrastructure improvement, the development of an integrated digital queuing system, intensive socialization, and the formation of collaborative teams across sectors (RSUD, government, TNI/POLRI, and the community). Conflict management training, periodic evaluation, and participatory leadership approaches are also needed to create sustainable service transformation. This study emphasizes that inclusive and transparent collaboration is the key to overcoming overcrowding and strengthening the safety of the hospital environment.